NETWORKING GOVERNANCE DALAM PENERAPAN SMART BRANDING CITRA NIAGA KOTA SAMARINDA - Perdana, Gusti Naufal Rizky; Ghazlina, Sonya Soraya; Pratama, Rizky; Prakoso, Cathas Teguh (Program Studi Administrasi Publik Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2021)
One of the efforts to make Samarinda City a livable city is through the optimization of Smart Branding. To realize Smart Branding in Samarinda City, a collaboration between all sectors, namely government, private, and society is needed. Citra Niaga has an area that displays the typical products of Samarinda City and as a public space for community activities. This has become a potential for Citra Niaga that describes the social and economic conditions of Samarinda City, so the application of Smart Branding in Citra Niaga is carried out to maximize the Citra Niaga area as an effort to realize the face of the City in Samarinda. This study used a qualitative descriptive method with data collection techniques using library research and field research through observation, interviews, and documentation. This study aims to describe the implementation of Networking Governance in the application of Smart Branding in Citra Niaga of Samarinda City and identify supporting also inhibiting factors in its implementation. The results show that the Government of Samarinda City has a goal in building a network in the implementation of smart branding in Citra Niaga to achieve the value of tourism, investment and the face of the city. The implementation of the network in Citra Niaga has been quite good among the government's internal circles, but there has been no involvement of the private sector specifically in this network.